The Identification of Molecular Ploidy Status of Abnormal Pronuclear Zygotes Reveals a Significant Number of Euploid Blastocysts Available for Conception - Blair R. McCallie; Mary E. Haywood; Lauren N. Henry; Rachel M. Lee; William B. Schoolcraft; Mandy G. Katz-Jaffe (Biomedicines)
Objective: Abnormally fertilized embryos are often discarded during in vitro fertilization due to the fact that known chromosomal ploidy abnormalities lead to implantation failure or pregnancy loss. The objective of this study was to determine if pronuclear numeration (PN) observed at fertilization check is representative of the true ploidy status of the subsequent developing blastocyst in order to maximize the number of viable embryos available for infertility patients and increase their chances of conception. Methods: Upon successful fertilization, pronuclear numeration was noted, and zygotes were cultured to the blastocyst stage. Biopsied trophectoderm cells were then lysed, and the isolated DNA was whole-genome amplified followed by library preparation. Next-generation sequencing was performed for PGT-A, and excess whole-genome amplified DNA was utilized for single nucleotide polymorphism beadchip array analysis. Results: At the time of fertilization check on day 1 of embryo development, when there were no visible pronuclei (n = 291), 56% of these 0PN blastocysts were confirmed to be diploid and normally fertilized. The remaining 41.9% were aneuploid, and 2.1% of the 0PN blastocysts contained only 23 haploid chromosomes. Upon analysis of the 1PN blastocysts (n = 217), just over a third (36.4%) only contained 23 haploid chromosomes (23XO), with another third (31.8%) identified as aneuploid, and surprisingly, the remaining third (31.8%) confirmed to be diploid and normally fertilized. In contrast, 50% of the 3PN blastocysts (n = 172) showed the presence of a third set of 23 parental chromosomes and were confirmed to be triploid (69XXY = 59.3% and 69XXX = 40.7%), with 41.9% identified as aneuploid and, interestingly, a small percentage (8.1%) confirmed to be diploid with normal fertilization. A very small proportion of biopsied blastocysts (0.63%) displaying the correct number of pronuclei for normal fertilization (2PN) were also identified as triploid with a third set of 23 parental chromosomes. To date, there have been 74 euploid embryo transfers from zygotes originally identified with an alternate pronuclear numeration, resulting in 16 ongoing pregnancies and 32 healthy live births, rates that match those typically observed with normally fertilized 2PN zygotes (>60%). Conclusions: A surprising number of blastocysts that were identified to have alternate pronuclear numeration at fertilization check on day 1 of embryo development were actually determined to be diploid with normal fertilization after molecular analysis. Accurate identification of haploid and tripoid zygotes is critical to prevent implantation failure and pregnancy loss and allows for the identification of all euploid embryos in a cohort, which has the potential to increase cumulative live birth rates for infertility patients.